The Role of Scavenger Receptor-A in Heat Shock Protein 27-mediated Atheroprotection: Mechanistic Insights into a Novel Anti-atherogenic Therapy - Raizman, Joshua E. (Université d'Ottawa / University of Ottawa, 2012)
Heat shock protein (HSP)27 is traditionally described as an intracellular chaperone and signaling molecule, but growing evidence suggests it is released from immune cells where it plays an anti-inflammatory role during atherogenesis. Previously, the O’Brien lab found that overexpression of HSP27 led to augmented HSP27 serum levels in female apolipoprotein E knockout (ApoE-/-) mice, attenuated atherogenesis, and inhibited macrophage foam cell formation via physical binding with scavenger receptor (SR)-A. However, the precise mechanism of atheroprotection remained elusive. This thesis sought to ascertain the mechanism(s) by which HSP27 prevents foam cell formation, and determine if SR-A, a key receptor involved in the uptake of lipid into macrophages, plays an important role in HSP27-mediated atheroprotection. Pre-treatment of human macrophages with recombinant HSP27 (rHSP27) inhibited acytelated low density lipoprotein (acLDL) binding and uptake independent from receptor competition effect. Reduction in uptake was associated with attenuation of expression of SR-A mRNA, total protein, and cell surface expression. To explore the signaling mechanism by which HSP27 modulated SR-A expression it was hypothesized that nuclear factor-kappa B (NF-kB), a major regulator of many atherosclerosis gene programs, is altered by extracellular HSP27. Indeed, rHSP27 markedly activated NF-kB signaling in macrophages. Using an inhibitor of NF-kBsignaling there was an attenuation of rHSP27-induced inhibition of SR-A gene and protein expression, as well as lipid uptake, suggesting that SR-A expression is regulated by NF-kB activation. Lastly, to investigate if SR-A is required for HSP27-mediated atheroprotection in vivo, ApoE-/- and ApoE-/-SR-A-/- mice fed a high fat diet were treated with rHSP25, the mouse orthologue of HSP27, or PBS for 3 weeks. While rHSP25 therapy equally reduced serum cholesterol levels in the mouse cohorts, aortic atherogenesis, assessed using en face and sinus cross-sectional analyses, was attenuated in ApoE-/- mice but not ApoE-/-SR-A-/- mice. In conclusion, rHSP27 inhibits foam cell formation by downregulating SR-A expression. This effect may be associated with NF-kB activation. Reductions in atherosclerotic burden by rHSP27 require SR-A, and are independent of changes in serum cholesterol levels, highlighting the importance of macrophage lipid uptake in atherogenesis. Results presented in this thesis demonstrate that SR-A is a major target for HSP27 atheroprotection in the vessel wall, and provide an impetus for further studies that investigate the potential therapeutic value of HSP27.
Keywords: scavenger receptor-A; heat shock protein 27; macrophage; foam cell formation; atherosclerosis; acetylated low density lipoprotein; NF-kappa b